La Riba Board Game / Mohd Shafiz Saharan ... [et al.] - Saharan, Mohd Shafiz; Jamaludin, Mohd Fazil; Adzahar, Khairul Azfar; Abd Hamid, Mohd Zulkhairi; Zainal, Nurdiyana Nazihah (Universiti Teknologi MARA, Kedah, 2023)
The product is called La Riba Board Game. The primary aim of creating this board game is to improve students' comprehension of the rules governing the exchange of ribawi materials. In addition, it teaches players the concept of ribawi item exchange and the rules and conditions that apply to it, enabling them to recognize ribawi items and understand their importance in Islamic finance. The implementation of game elements and mechanics in educational settings, known as gamification in learning, serves the purpose of enhancing learning experiences by making them more interactive, engaging, and effective. It may be relatively rare to find a board game designed specifically for teaching about riba. To close this gap, the researcher is being innovative and adapting the gamification method to explore this topic and provide a more comprehensive education on Islamic Finance. The game will teach students about ribawi items, their specific exchange regulations, and the importance of conducting transactions fairly, all presented in a creative and engaging manner. Through this method, students will learn these concepts in an interesting and captivating way. After successfully completing the game, students will provide their feedback and responses, which will be used by the researcher for improvement to ensure the game is appropriately challenging, enjoyable to play, and wellbalanced. Hence, the findings show that the learning activity through this board game can contribute to several benefits, including improved understanding of Islamic finance, engaging and interactive learning, practical application of knowledge, skill development, and increased awareness and interest in Islamic finance. Through gameplay, students can apply Islamic finance principles, develop critical thinking and decision-making skills, and become more interested in this field.